A comprehensive review on the potential therapeutic benefits of prospective probiotic Christensenella minuta - Yueyao Fan; Yuhang Xiao; Shiqing Zhang; Weibin Bai; Jiali Chen (Food Science and Human Wellness)
Bacterial family Christensenellaceae performed high heritability and associated with human health status. Numerous studies observed that the abundance of Christensenellaceae could be significantly reduced in patients with intestinal diseases or metabolic disorders, inferred that it may be treated as an effective biomarker. Christensenella minuta was the first member of Christensenellaceae family isolated from human fecal samples. Accumulating evidences suggested that C. minuta may demonstrate a positive bio-therapeutic effects toward unhealthy status. Hence, this review aimed to systematically summarize the characterization of Christensenellaceae under specific health or diseases, and discover its promising application. Besides, the latest studies on the pharmacological research of C. minuta also summarized. Current important literatures grasped the potential health benefits of C. minuta in managing metabolic disorders, gut ecosystem, and inflammation. Whereas, several critical knowledge gaps about the safe and clinical application remain should be addressed in future verification. C. minuta is worthy to be elevated as the next prospective probiotic star in nutraceutical or medical field and should not be overlooked.